2022
DOI: 10.1371/journal.pone.0274732
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation in shrunken2 gene affecting kernel sweetness in exotic-and indigenous-maize inbreds

Abstract: Sweet corn has become a popular food worldwide. It possesses six-times more sugar than field corn due to the presence of recessive shrunken2 (sh2) gene. Despite availability of diverse sweet corn germplasm, comprehensive characterization of sh2 has not been undertaken so far. Here, entire Sh2 gene (7320 bp) among five field corn-(Sh2Sh2) and six sweet corn-(sh2sh2) inbreds was sequenced. A total of 686 SNPs and 372 InDels were identified, of which three SNPs differentiated the wild-(Sh2) and mutant-(sh2) allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Globally, the preference and demand of sweet corn has increased steadily in the last decade [17]. Sweet corn consumed as fresh at milky stage possesses nutritional bene ts for human health [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, the preference and demand of sweet corn has increased steadily in the last decade [17]. Sweet corn consumed as fresh at milky stage possesses nutritional bene ts for human health [13].…”
Section: Discussionmentioning
confidence: 99%
“…Mutant sh2-based sweet corn possesses six-fold higher sucrose and suitable for prolonged storage and transportation [16]. Large number of sh2-based sweet corn hybrids have been released for commercial cultivation worldwide [17].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 48 genotypes examined in the study formed 42 haplotypes. Chhabra et al [49] identified 44 haplotypes, Katral et al [52] identified 41 haplotypes and Chhabra et al [55] identified 47 haplotypes of 48 maize genotypes based on su1, Zmfatb and sh2 gene-based markers, respectively and Shin et al [56] identified 14 haplotypes of 15 sweet corn accessions using SNP based markers. Sequencing technologies has made it simpler to generate haplotype information, which aids in determining ancestry and demographic history [57].…”
Section: Allelic Variations In Lpa1 Gene In Maize Genotypesmentioning
confidence: 99%
“…However, only four genes are commonly used in sweet corn breeding: sh2 and bt2, which are categorized as 'super sweet' corn, and sugary-1 (su1) and sugary enhancer (se), which are categorized as general sweet corn (Santos et al 2014;Ojo et al 2020). Recessive sh2-based sweet corn genotypes, also known as 'extra sweet corn' or 'super sweet,' accumulate six times more sugar than normal corn at the milky ripe stage (Chhabra et al 2022) Sweet corn is one of the most famous vegetables in Asian countries like Indonesia (Dermail et al 2022), as it can be consumed fresh or processed as an ingredient for the food industry (Alan et al 2013). Sweet corn has the thirdlargest planted area of a vegetable in Indonesia, after chili peppers and shallots.…”
Section: Introductionmentioning
confidence: 99%